Speech and silence of the marginalised communities: The reading of Dina Zaman's text utilising transitivity analysis / Nazima Versay Kudus - Kudus, Nazima Versay (2022)
Feminism's contributions include bringing attention to the ways in which language has functioned to establish and maintain gender roles, one of which is the investigation of speech and silence. The objective of this paper is to analyze the speech patterns (if any) of the female characters categorized as the 'other' in Dina Zaman's short stories and chart to what extent they are given voices in a narratology. Sara Mills' feminist stylistic methodology of transitivity or linguistic structuring of actions and verbs in the language allow readers to see the participants' involvement via language. The analyses reveal that the author has deconstructed the ways in which Malay women characters are commonly represented in narrative texts. Writings by the likes of Dina Zaman should be an accolade to the unrepresented women who exist in our society and in fact do not wish to be marginalized.